Fractal solar cell array for enhanced energy production: applying rules underlying tree shape to photovoltaics. (29th July 2020) - Sim, Yeon Hyang; Yun, Min Ju; Cha, Seung I.; Lee, Dong Yoon
Abstract : Plants and photovoltaics share the same purpose as harvesting sunlight. Therefore, botanical studies could lead to new breakthroughs in photovoltaics. However, the basic mechanism of photosynthesis is different to semiconductor-based photovoltaics and the gap between photosynthesis and solar cells must be bridged before we can apply the botanical principles to photovoltaics. In this study, we analysed the role of the fractal structures found in plants in light harvesting based on a simplified model, rotated the structures by 90° and applied them to fractal-structured photovoltaic Si solar cell arrays. Adoption of botanically inspired fractal structures can result in solar cell arrays with omnidirectional properties, and in this case, yielded a 25% enhancement in electric energy production. The fractal structure used in this study was two-dimensional and symmetric; investigating and optimizing three-dimensional asymmetric fractal structures would further enhance the performance of photovoltaics. Furthermore, this study represents only the first step towards the development of a new type of photovoltaics based on botanical principles, and points to further aspects of botanical knowledge that could be exploited, in addition to plant fractal structures. For example, leaf anatomy, phyllotaxis and chloroplastic mechanisms could be applied to the design of new types of photovoltaics.